The Effect of Total Asset Turnover, Debt to Equity Ratio, Net Profit Margin, and Firm Size on Profitability in Company of Consumer Goods Industry - Jesica Jania; Eso Hernawan (Komunitas Dosen Indonesia, 2022)
The aims of this research is to determine the effect of TATO, DER, NPM, Firm Size on Profitability. Method fordetermining the sample is by taking objects according to certain criteria, namely the purposive sampling. This research uses Eviews 10 software for data processing with various kinds of data analysis tests. The results of this research indicate two independent variables do not have a partial effect on profitability, such as TATO and Firm Size. There are also two independent variables that have a partial effect on profitability, such as DER and NPM. Meanwhile, 67.5% of the independent variables TATO, DER, NPM and Firm Size have an influence simultaneously on profitability and the remaining 32.5% are variables not examined.